Moderating Role of Organizational Support in Thriving at Work and Job Performance among Telecom Employees - Rasheed, Hafsa; Arbab, Manika; Zia, Saadia (Pakistan Journal of Humanities and Social Sciences, 2025)
This study was conducted to analyze the influence of Thriving at Work on Job Performance among telecom employees in Pakistan’s telecommunication sectors with a moderating role of organizational support. A correlational research design was used with survey method. Data was collected from 176 telecom representatives. Three scales were used in the current study. First scale was used of Thriving at Work developed by Micheal Dam with 8 items, the second scale was used of Job performance by Abdullah Caliskan and Ozlem Korogulu with 11 items, and third scale was used of organizational support developed by Eisenberger and Stinglhamber with 16 items. Data was analyzed through SPSS and moderating analysis was done through process macro. The findings indicated a positive correlation between thriving at work and Job Performance. Employees who reported higher levels of thriving showed high Job Performance, with good job engagement and productivity. Organizational support significantly played a moderating role in thriving at work and job performance. The positive effect of thriving on job performances was stronger for employees who seeming higher levels of organizational support. The findings highlighted the importance of fostering a thriving work environment to enhance job performance. Improving organizational support, organizations enhances the positive effect of thriving at work, leading to increased job performance.